Significant risk of COVID-19 and related-hospitalization among patients with adrenal insufficiency: A large multinational survey - Yedinak, Christine; Ross, Ian Louis (Frontiers in Endocrinology, 2022)
Objective To determine self-reported incidence and potential risk factors for COVID-19 in patients with adrenal insufficiency (AI). Methods A 27-item AI survey was developed for AI and COVID-19 status, vetted by specialists and patients, and distributed via social media, websites, and advocacy groups. Participation was voluntary and anonymous. Data were collected from September 20th, 2020 until December 31st, 2020. Results Respondents (n=1291) with self-reported glucocorticoid treatment for AI, completed the survey, with 456 who reported having symptoms and were screened for COVID-19 during 2020; 40 tested positive (+ve), representing an 8.8% incidence. Of the COVID-19+ve, 31 were female (78%), with mean age of 39.9 years. COVID-19 among AI patients occurred most commonly in those aged 40–59 years (n=17; 42.5%); mean time since AI diagnosis was 13.5 years (range 0.2−42.0 years). Pulmonary disease, congenital adrenal hyperplasia, and higher maintenance doses of glucocorticoids were significantly associated with +ve COVID-19 (p=0.04, p=0.01, and p=0.001, respectively. In respondents the cumulative incidence of COVID-19+ve during 2020 was 3.1%; greater than the 1.03% worldwide-incidence reported by WHO, by December 31st, 2020. There was a 3-fold (95% CI 2.16-3.98) greater relative risk (RR) of COVID-19 infection and a 23.8- fold (95% CI 20.7-31.2) RR of hospitalization in patients with AI, compared with the global population. Conclusion A markedly raised RR of COVID-19 and hospitalization in respondents reporting chronic AI was detected. We found that a diagnosis of congenital adrenal hyperplasia, age>40 years, male gender, pulmonary disease, and higher maintenance doses of glucocorticoids were associated with greatest risk.